Assessment of the Impact of Compulsory Insurance on Ensuring Economic Growth (the Case of the RA) - Hakobyan, Gagik («Տնտեսագետ» հրատ․)
In the framework of this study, we have studied the works of many international authors related to the identification of the connections between the insurance market and economic growth, after which we have carried out our analysis using the Granger causality test model. The relationships between compulsory insurance and economic growth of the RA, using annual data throughout 2011-2022, have been examined in this paper. During the research descriptive statistical analysis and econometric models have been applied. The significance of the insurance-growth relationship has been better understood thanks to this study, which also includes other methods used in recent scientific publications. The following findings are the outcome of the research. • In Armenia we have a high correlation between voluntary and compulsory insurance sectors and economic growth indicators. • The Granger test has demonstrated a one-way causal relationship between GDP and voluntary insurance and bidirectional causality between compulsory insurance premiums and GDP variables. As a result of this research, the positive consequences of the introduction of a new type of compulsory insurance in the processes of ensuring economic growth have been substantiated.
Keywords: Finance